2019
DOI: 10.1177/1932202x19869006
|View full text |Cite
|
Sign up to set email alerts
|

Letting Go of the Middle Years Programme: Three Schools’ Rationales for Discontinuing an International Baccalaureate Program

Abstract: International Baccalaureate Middle Years Programme (MYP) is recognized for its rigor, inquiry-based learning, and development of academic skills. While it is growing in popularity worldwide, some schools have discontinued the program. Literature on the reasons why schools discontinue the MYP is limited. Using a qualitative case study design, we examined the perspectives of school leaders, former MYP coordinators, and experienced MYP teachers at three private and public Australian schools to find out why they d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There is also limited research available within the Australian context that examines students' learning challenges within the MYP. This paper addresses these research gaps and builds on a previous publication (Dickson, Perry & Ledger, 2020) that considered the reasons why a group of Australian schools discontinued the MYP. In this paper, we focus exclusively on stakeholder insights about the impact of the MYP on student learning.…”
Section: Aims and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also limited research available within the Australian context that examines students' learning challenges within the MYP. This paper addresses these research gaps and builds on a previous publication (Dickson, Perry & Ledger, 2020) that considered the reasons why a group of Australian schools discontinued the MYP. In this paper, we focus exclusively on stakeholder insights about the impact of the MYP on student learning.…”
Section: Aims and Research Questionsmentioning
confidence: 99%
“…The research reported in this paper is part of a larger study that examined the reasons why some schools in Australia chose to discontinue the IB Middle Years Programme (MYP). The study found that schools discontinued the MYP due to challenges with assessment, pedagogy, and alignment with the national curriculum (Dickson, 2019; Dickson, Perry & Ledger, 2020). When explaining why their school chose to discontinue the MYP, participants noted both benefits and challenges for student learning and their own teaching practice.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, however, a small but increasing number of schools are discontinuing IB programmes, including in the UK (Bunnell, 2015) and Australia (Dickson et al, 2020). To date, the reasons why school leaders discontinue an IB programme on behalf of their school have not been examined.…”
Section: Challenges Of the International Baccalaureate Middle Years Programme: Insights For School Leaders And Policy Makersmentioning
confidence: 99%
“…Intuitively, parental choice and its concomitant cost must be weighed against the programmes' perceived elitist/prestigious benefits. Further, while the IB programme may be considered prestigious because they proffer benefits such as the greater probability of university entrance as Caspary et al (2015) argue, many schools in Australia and elsewhere are abandoning the programme due to leadership, teacher and organisational problems that render them costly to administer (Dickson et al, 2019). Another study by the same authors (Perrry et al, 2018) finds the financial cost of the IB programme outweigh its benefits.…”
Section: Tuition Fee Comparison As a Marker Of Elitismmentioning
confidence: 99%